2021
DOI: 10.1186/s12920-021-00930-1
|View full text |Cite
|
Sign up to set email alerts
|

A pan-cancer study of selenoprotein genes as promising targets for cancer therapy

Abstract: Background The most important health benefit of selenium (Se) is in the prevention and control of cancer. Glutathione peroxidases (GPXs) and thioredoxin reductases (TXNRDs) are selenoenzymes that are thought to play a role in oxidative stress. The differential expression of genes of the TXNRD and GPX families is closely related to carcinogenesis and the occurrence of cancer. This study comprehensively analyzed the expression profiles of seven genes in the TXNRD and GPX families, in terms of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 75 publications
0
36
0
1
Order By: Relevance
“…For example, the RBP CLUH (clustered mitochondria homologue), together with other RBPs, have been shown to regulate the expression of a mitochondrial protein network that become important under conditions of nutrient deprivation (67). Glutathione metabolism is key to the disposition of super-oxides, which are produced at high levels during chemotherapy (68). CRD-BP and its close paralogue, IGF2BP3, have beeen shown to enhance drug resistance for tumor cells (69,70).…”
Section: Comparison Of the Results Of Esp Purification Of Crd-bp Binding Rnas With Other Studiesmentioning
confidence: 99%
“…For example, the RBP CLUH (clustered mitochondria homologue), together with other RBPs, have been shown to regulate the expression of a mitochondrial protein network that become important under conditions of nutrient deprivation (67). Glutathione metabolism is key to the disposition of super-oxides, which are produced at high levels during chemotherapy (68). CRD-BP and its close paralogue, IGF2BP3, have beeen shown to enhance drug resistance for tumor cells (69,70).…”
Section: Comparison Of the Results Of Esp Purification Of Crd-bp Binding Rnas With Other Studiesmentioning
confidence: 99%
“…GPX consists of eight antioxidant enzymes, and their main function is to defend the organism against oxidative stress. A previous study revealed that GPXs have antitumor effects because they block reactive oxygen species (ROS) and regulate the redox signaling system, which plays a key role in tumor growth (Wu et al, 2021). Hydroperoxides stimulate cell proliferation and migration, but excessive hydroperoxides lead to cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the somatic mutations in adjacent normal tissues, we found that somatic mutations in GPX2 and PPDPF initially occurred in normal tissues patients and accumulated in tumors. GPX2 plays a role in protecting cells against oxidative damage ( 56 ), and PPDPF is a probable regulator of exocrine pancreas development ( 57 ). Abnormal expression of GPX2 might facilitate tumorigenesis and result in poor progress in adrenocortical cancer, kidney papillary cell carcinoma, and uveal melanoma ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…GPX2 plays a role in protecting cells against oxidative damage ( 56 ), and PPDPF is a probable regulator of exocrine pancreas development ( 57 ). Abnormal expression of GPX2 might facilitate tumorigenesis and result in poor progress in adrenocortical cancer, kidney papillary cell carcinoma, and uveal melanoma ( 56 ). Aberrant PPDPF expression was correlated with poor prognosis in hepatocellular carcinoma ( 58 ).…”
Section: Discussionmentioning
confidence: 99%